TANGGUNG JAWAB NEGARA TERHADAP ORANG ASING MENURUT HUKUM INTERNASIONAL DAN HUKUM NASIONAL INDONESIA - Siti Sarra; Sutiarnoto Sutiarnoto; Jelly Leviza (Journal of USU International Law, 2017)
RESPONSIBILITIES OF STATE TO PEOPLE BY INTERNATIONAL LAW AND INDONESIAN NATIONAL LAW Abstract Siti sarra* Sutiarnoto** Jelly leviza*** As the subject of International Law, countries have international rights and obligations. The state's responsibility to the individual is substantially determined by that country's territory and the nationality of the individual concerned. As for the problem in this research is how the protection against foreigners based on national law,how to protect foreigners under international law, and how the state is responsible for foreigners according to international law, with the title